Ekspolorasi Kompetensi Literasi Sains Siswa Sekolah Dasar - Muttaqin, Mochamad Iqbal; Koeshandayanto, Supriyono; Masfufah, Aynin (Universitas Nahdlatul Ulama Blitar, 2024)
Research on the profile of scientific literacy was conducted on grade IV students at SDN Kademangan 05, Blitar Regency. The approach taken is descriptive qualitative. Data collection methods using interviews and observation. Data analysis with triangulation and member checking. The research results show that the Science Literacy Profile at SDN Kademangan 05 Blitar Regency based on the science literacy component has three aspects and eight indicators of achievement. First, the aspect of identifying scientific issues: with indicators that students can do, such as students starting to be able to recognize issues that can be investigated scientifically, students starting to be able to identify keywords to search for scientific information, students starting to be able to mention the steps of scientific investigation; Second, the aspect of explaining phenomena scientifically, with indicators that students can do. Students begin to be able to apply scientific knowledge. Students begin to be able to provide explanations related to scientific phenomena. Third, the aspect of using scientific evidence, with indicators that students can use. Students begin to be able to draw conclusions based on the interpretation of the data presented. Students begin to be able to identify long-term consequences related to the development of science. The limitations of this research only look at it with a qualitative approach so that in the future research is needed to quantitatively evaluate the literacy skills of students at SDN Kademangan 05 Blitar Regency.